#StayHome and #TravelTomorrow – (De)marketing Travel Experiences during the Covid-19 Pandemic : Multimodal Discourse Analysis of Tourism Promotional Videos - Ristimäki, Mirka (My University, 2021)
This thesis studies tourism representations and (de)marketing strategies in promotional videos created by 20 Destination Marketing Organizations (DMOs) during the Covid-19 pandemic in Spring 2020. The objective of the study is to examine how the multimodal resources of the videos contribute to destination marketing and are influenced by the challenging conditions imposed on travel. These aspects provide an interesting angle from which to examine tourism promotion and the representational metafunction of language and visual communication. The methods of multimodal discourse analysis (Halliday and Matthiessen [1985] 2014; Kress and van Leeuwen 1996; 2006; Royce 1998) are utilized in the analysis of transitivity and representational meanings derived from the voiceover and visual shots of the videos. The discussion of the results is based on existing studies on tourism representations and place marketing. These elements provide the basis for analysing each semiotic mode separately, after which intersemiotics is considered while comparing the DMOs’ approaches to each other. Four different approaches to destination (de)marketing were identified based on the verbal transitivity features of the videos, constructed mainly around material, relational, and mental processes. Based on the emphasis on destination attractions and attributes and other ways of creating demand, such as showcasing the spirit and culture of the destination, the representations found repeat the tendencies of tourism promotion. At the same time, the results provide examples of place demarketing through verbal incentives to divert demand realized through direct statements and the abstraction of language. The absence of represented destination qualities in favour of more important basics of life was also found to be a frequent theme in the videos. These verbal meanings were complemented by visual features of the videos, usually either by repeating similar meanings or exemplifying them in different ways. Essential features of the destinations were utilized to place emphasis more strongly on their attractions, mostly through analytical, symbolic, and narrative representations of nature, culture, hosts, and guests. Temporal representations, on the other hand, were more tied to the pandemic context. The study suggests that the methods of multimodal discourse analysis are useful in providing evidence on promotional strategies and tourism representations, as well as in examining aspects of video material. Overall, multimodality proves to be a potentially effective tool for place marketing.
Keywords: Multimodal Discourse Analysis, Functional Linguistics, Tourism Representation, Destination Marketing, Covid-19 Pandemic